PENDAMPINGAN KONSELING PADA REMAJA MELAKUKAN SELF HARM - Rohimah, Siti; Fatiyatus, Siti; Msarujahid, Kasori; Citrasari, Novenna; WIjaya, Muria (STKIP Pesisir Selatan, 2025)
Many phenomena of self-harm lately have occurred in the lives of adolescents when adolescents are unable to deal with disappointment, sadness and anger. This research uses a qualitative research method with the